Combined Effects from Solvation and Nuclear Quantum Fluctuations on Autoionization Mechanisms in Aqueous Clusters - Turi, Laszlo (2020)
Using path-integral molecular dynamics simulations, we examine isomerization paths involving collective proton transfers in [H2O]5 and [H2O]8 clusters under cryogenic conditions. We focused attention on combined effects derived from solvation and nuclear quantum fluctuations on the characteristics of free energy barriers and relative stabilities of reactants and products. In particular, we analyzed two different processes: the first one involves the exchange of donor-acceptor hydrogen bond roles along cyclic moieties, whereas the second one corresponds to charge separation leading to stable [H3O]+[OH]- ion pairs. In the first case, the explicit incorporation of quantum tunneling introduces important modifications in the classical free energy profile. The resulting quantum profile presents two main contributions, one corresponding to compressions of O-O distances and a second one ascribed to nuclear tunneling of the light protons. Solvation effects promote a moderate polarization of the cyclic structures and a partial loss of concertedness in the collective modes, most notably, at the onset of tunneling. Still, the latter effects are also sufficiently strong to promote the stabilization of ion pairs along the classical trajectories. In contrast, the explicit incorporation of nuclear quantum fluctuations leads to charge separated configurations that are marginally stable. As such, the latter states could also be regarded as short-lived intermediate states along the reactive exchange path.